The prioritisation of curable sexually transmitted infections among pregnant women in Zambia and Papua New Guinea: Qualitative insights. - Lisa M Vallely; Kelvin Kapungu; Alice Mengi; Mike Chaponda; R Matthew Chico; Michaela A Riddell; Andrew J Vallely; William Pomat; Eva Cignacco; Nicola Low; Angela Kelly-Hanku (Public Library of Science (PLoS), 2024)
Curable sexually transmitted infections (STIs) are neglected in public health policy, services and society at large. Effective interventions are available for some STI but seem not to be prioritised at global, regional or local levels. Zambia and Papua New Guinea (PNG) have a high burden of STIs among pregnant women but little is known about the prioritisation of STI treatment and care among this group. We undertook a qualitative study to explore how STIs are prioritised among pregnant women in local health systems in Zambia and PNG. Semi-structured interviews were conducted with 19 key informants-health care workers providing antenatal care, and policy and programme advisers across the two countries. Audio recordings were transcribed and translated into English and stored, managed, and coded in NVivo v12. Analysis used deductive and inductive thematic analysis. Findings were coded against the World Health Organization health system building blocks. Participants spoke about the stigma of STIs at the community level. They described a broad understanding of morbidity associated with undiagnosed and untreated STIs in pregnant women. The importance of testing and treating STIs in pregnancy was well recognised but many spoke of constraints in providing these services due to stock outs of test kits for HIV and syphilis and antibiotics. In both settings, syndromic management remains the mainstay for treating curable STIs. Clinical practice and treatment were not in alignment with current STI guidelines in either country, with participants recognising the need for mentorship and in-service training, as well as the availability of commodities to support their clinical practice. Local disruptions to screening and management of syphilis, HIV and other curable STIs were widely reported in both countries. There is a need to galvanise priority at national and regional levels to ensure ongoing access to supplies needed to undertake STI testing and treatment.